Rekayasa Pengembangan Agribisnis Stroberi Organik Di Sulawesi Utara Dalam Era Agribisnis 4.0 - Loho, Agnes Estephina; Rengkung, Leonardus Ricky; Mandei, Juliana Ruth (Sam Ratulangi University, 2023)
This research aims to design the development of an organic strawberry agribusiness in North Sulawesi through the pentahelix collaborative engineering. This research was conducted from March to September 2022. The method used in this research is a survey method. The selection of the research location was carried out purposive, namely the area which is the center of organic strawberry production in North Sulawesi. The data used in this study are primary data and secondary data. Primary data includes: (1) performance of organic strawberry agribusiness, (2) synergy of strawberry agribusiness subsystems in North Sulawesi, and (3) role of pentahelix in organic strawberry development. Secondary data is in the form of supporting data for this research. The data collection techniques used were (1) using questionnaires, (2) observation, (3) interviews, (4) Focus Group Discussion (FGD) and (5) documentation. The analysis used in this research is descriptive analysis. The results of the study show that the application of organic farming has not been fully implemented because respondents still use chemical fertilizers and pesticides. Strong integration of strawberry agribusiness development has not been created between sub-systems either vertically or in terms of. Agribusiness development desigm follows the Services Rationalization collaboration pattern, namely increasing the role of the service sector that is related to agribusiness subsystems. Increasing the role in the form of increasing the role of academics as a attracting sector and as a facilitator, the role of the Government as a supporting sector, the role of the media as a source and dissemination of information, the role of farmer associations as a driving sector and the business sector which consists of all agribusiness subsystems other than agriservices as the implementing sector. Further engineering in the Pentahelix collaboration in the development of strawberry agribusiness then put forward three main components, namely the business component, the academic component, and the support component.